Increasing the Growth and Yield of Cantaloupe (Cucumis melo Var. Cantalupensis L.) with the Combination of Planting Media and Seaweed Extract with Drip Irrigation Hydroponics - Arya Windayah; Didik Sutomo Pribadi; Sutini (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Cantaloupe (Cucumis melo var. Cantalupensis L.) is a high-value horticultural crop, popular among consumers for its sweet taste and distinctive aroma. Hydroponic cultivation of cantaloupe using a drip irrigation system offers a promising solution to overcome land limitations, particularly in urban areas. The success of this system is largely influenced by the type of planting medium and the provision of appropriate nutrients. This study aimed to evaluate the effects of different combinations of planting media and seaweed extract doses on the growth and yield of cantaloupe plants. The experiment was conducted from October to December 2024 at the Puspa Lebo Greenhouse, Lebo Village, Sidoarjo District, Sidoarjo Regency, located at an altitude of 4 meters above sea level, with daily temperatures ranging from 26.9°C to 30.4°C. A completely randomized design (CRD) with two factors was used: planting media (cocopeat, rice husk charcoal, and a mixture of cocopeat and rice husk charcoal) and seaweed extract doses (0, 5, 10, and 15 g/plant). The results indicated that cocopeat as a planting medium had a significant positive effect on fruit weight. Additionally, a seaweed extract dose of 5 g/plant significantly enhanced vegetative growth parameters, including plant length and leaf number. In the generative phase, a dose of 10 g/plant significantly influenced the timing of flower emergence and harvest age.